Ways of Implementation in the Future of the Formation of Information and Modeling Skills in Students of the Technical Direction (Eurasian Scientific Herald, 2022)
This scientific article presents opinions on the stages of formation of informationmodeling skills in technical students, taking into account the use of information communication technologies.